Sequential Delivery of Cryogel Released Growth Factors and Cytokines Accelerates Wound Healing and Improves Tissue Regeneration - Jimi, Shiro; Jaguparov, Alexandr; Nurkesh, Ayan; Sultankulov, Bolat; Saparov, Arman (Frontiers in Bioengineering and Biotechnology, 2020)
Growth factors that are secreted by cells play a crucial role in the complex physiological reaction to tissue injury. The ability to control both their detrimental and beneficial effects will help accelerate wound healing and improve tissue regeneration. In this study, the sequential targeted delivery of growth factor combinations with regulatory functions on inflammation and tissue regeneration was examined using an internal splint wound healing model. Four examined growth factors were effectively incorporated into a novel chitosan-based cryogel, which offered a controlled and sustained release of all factors while maintaining their biological activities. The cryogels with incorporated growth factors were placed on the wound surface on day 0 (IL-10 and TGF-β) and day 3 (VEGF and FGF) after wound initiation. Although wound area gradually decreased in all groups over time, the area in the cryogel group with growth factor combinations was significantly reduced starting on day 7 and reached about 10% on day 10, as compared to 60-65% in the control groups. Sequential delivery of growth factors enhanced granulation tissue formation, as well as functional neovascularization, leading to regenerative epithelialization. Collectively, the chitosan-based cryogel can serve as a controlled release system for sequential delivery of several growth factors to accelerate tissue repair and regeneration.